PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPS PESERTA DIDIK DI KELAS VIII-6 MTS MESRA PEMATANGSIANTAR T.A 2023/2024 - Syifa Salsa Bila; Ahmad Fakhri Hutauruk; Satria Chandra Chandra (Prodi Pendidikan Sejarah FKIP USI, 2026)
The Problem-Based Learning model can be defined as a series of learning activities that emphasize the scientific process of solving problems. The main question in this study is whether the Problem-Based Learning model has an effect on the social studies learning outcomes of students in grades VIII-6 at MTs Mesra Pematangsiantar. The aim was to determine the effect of the Problem-Based Learning model on the social studies learning outcomes of students in grades VIII-6 at MTs Mesra Pematangsiantar. This research method used a Pre-Experimental Design with a One-Group Pre-Test-Post-Test Design, a research method that uses only one class as an experimental class without a comparison class (control class). This method serves to determine whether there is an improvement in students' history learning outcomes following the application of the Problem-Based Learning model to students in grades VIII-6 at MTs Mesra Pematangsiantar. Based on the analysis results obtained using the Shapiro-Wilk normality test at a significance level of 0.05, the obtained value was 0.120, indicating a normal distribution, as 0.120 ≤ 0.05. This is supported by the results of the normality test, which compares Lhitung< Ltabel. Lhitung is 0.136, and Ltabel is 0.155. Therefore, it can be concluded that the data is normally distributed, with 0.136 < 0.155.Furthermore, the results of the t-test hypothesis test revealed a significant relationship between the independent variable (Problem Based Learning model) and the dependent variable (social studies learning outcomes).This is evident by the calculated t value > t tabel value, or 20.681 > 1.697 at the significance level. Therefore, t is accepted and 0 is rejected. Thus, it is proven that there is a significant influence of the use of the Problem-Based Learning model on the social studies learning outcomes of grade VIII-6 students at MTs Mesra Pematangsiantar.